The short-term seismicity of the Central Ionian Islands (Greece) studied by means of a clustering model. Issue 2 (22nd October 2019) - Mangira, Ourania; Console, Rodolfo; Papadimitriou, Eleftheria; Murru, Maura; Karakostas, Vasilios
SUMMARY: Earthquake clustering in the area of Central Ionian Islands (Greece) is statistically modelled by means of the Epidemic Type Aftershock Sequence (ETAS) branching model, which is the most popular among the short-term earthquake clustering models. It is based upon the assumption that an earthquake is not fully related to any other one in particular, but rather to both all previous events, and the background seismicity. The close temporal proximity of the strong ($M \ge 6.0$ ) events in the study area offers the opportunity to retrospectively test the validity of the ETAS model through the 2014 Kefalonia doublet ( M w 6.1 and M w 6.0) and the 2015 Lefkada aftershock sequences. The application of a physics-based earthquake simulator to the local fault system produced a simulated catalogue with time, space and magnitude behaviour in line with the observed seismicity. This catalogue is then used for the detection of short-term interactions between both strong and smaller events and the comparison between the two cases. The results show that the suggested clustering model provides reliable forecasts of the aftershock activity. Combining the ETAS model and the simulator code, though, needs to be more deeply examined since the preliminary results show some discrepancy between the estimated model parameters.